A scoop net equipped with an underwater anti-oil-fouling filter for fast cleanup of low-sulfur fuel at low temperature. Issue 6 (December 2022) - Seo, Yu Jin; Han, Nara; Kim, Hee Ju; Choi, Ji Hee; Koo, Hye Young; Yu, Chengzhong; Choi, Won San
Abstract: A scoop net equipped with an underwater anti-oil-fouling (AOF) filter was tested for the cleanup of low-sulfur fuel (LSF). An underwater AOF filter [fabric/oxidized carbon soot (O-CS)/polyvinyl alcohol-Konjac glucommannan (PVA-KGM)] possessing a partially dissoluble surface was prepared by the stepwise coating of O-CS and PVA/KGM onto different fabrics. The effects of the molecular weight (MW) of PVA, thickness of the filter, and water temperature on the underwater AOF performance of the filter were investigated. Since the fabric (3 mm)/O-CS/L -PVA-KGM filter showed the highest water absorption capacity (6.23 g/g) and water content (96.4%) after 1 h, this filter showed the lowest amount of residual LSF (Abs: 0.004 at 275 nm) and the best long-term AOF stability after 30 cycles at 20 °C. This filter still showed excellent AOF performance (Abs: 0.008 at 275 nm) and high flux (66, 793 L/m 2 h) at 4 °C due to high water absorption capacity/contents and large pores/relatively long multichannels, respectively. Graphical Abstract: ga1 Highlights: A scoop net equipped with an underwater anti-oil-fouling (AOF) filter is prepared. The filter shows the highest water absorption capacity (6.2 g/g) and content (96.4%). The filter has the best long-term AOF stability at 20 °C for the cleanup of LSF. The filter still shows excellent AOF performance and high flux (66, 793 L/m 2 h) at 4 °C.